2020
DOI: 10.5812/aapm.100563
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium Sulfate and Clonidine; Effects on Hemodynamic Factors and Depth of General Anesthesia in Cesarean Section

Abstract: Background: Making stable hemodynamic and also durable unawareness is a daily challenge in the setting of general anesthesia in women who undergo surgical delivery of neonate and have limitations to receive opioids derivatives. Objectives: We aimed to evaluate the effects of magnesium sulfate and clonidine on hemodynamic changes and depth of anesthesia and in mentioned mothers and also in neonatal APGAR index. Methods: Current randomized, double-blind controlled trial study was conducted among a total of 360 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Magnesium is the second important intracellular cation that plays a crucial role in enzymatic activity and neurochemical transmission at the synaptic junction of muscles. Besides preventing eclamptic seizures and having cardiovascular effects, a new role for this drug in anesthesia has been defined in recent years (28)(29)(30). The antinociceptive effects of magnesium in managing acute and chronic pain have been established in numerous studies (31)(32)(33).…”
Section: Discussionmentioning
confidence: 99%
“…Magnesium is the second important intracellular cation that plays a crucial role in enzymatic activity and neurochemical transmission at the synaptic junction of muscles. Besides preventing eclamptic seizures and having cardiovascular effects, a new role for this drug in anesthesia has been defined in recent years (28)(29)(30). The antinociceptive effects of magnesium in managing acute and chronic pain have been established in numerous studies (31)(32)(33).…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were obtained by Bajwa et al (38), as they found that epidural clonidine in CS resulted in shorter onset of analgesia with a longer duration, but with more bradycardia and hypotension occurrence, which may be detrimental for parturients. Rajabi et al (39) reported that when intravenous infusion of magnesium or clonidine were used in combination with GA in CS, once at the time of the induction, they had favorable hemodynamic and anesthetic profile with no risk to the neonate. This study had some limitations.…”
Section: Discussionmentioning
confidence: 99%
“…During pregnancy, general anesthesia is a complicated process. MgSO4 or clonidine infused intravenously would maintain hemodynamic parameters and deepen general anesthesia in the context of surgical delivery, posing no additional acute danger to newborns [ 18 , 47 ].…”
Section: Reviewmentioning
confidence: 99%